Occlusion culling and calculation for a computer generated hologram using spatial frequency index method. (22nd September 2015) - Zhao, Kai; Huang, Yingqing; Yan, Xingpeng; Jiang, Xiaoyu
Abstract: A spatial frequency index method is proposed to cull occlusion and generate a hologram. Object points with the same spatial frequency are put into a set for their mutual occlusion. The hidden surfaces of the three-dimensional (3D) scene are quickly removed through culling the object points that are furthest from the hologram plane in the set. The phases of plane wave, which are only interrelated with the spatial frequencies, are precomputed and stored in a table. According to the spatial frequency of the object points, the phases of plane wave for generating fringes are obtained directly from the table. Three 3D scenes are chosen to verify the spatial frequency index method. Both numerical simulation and optical reconstruction are performed. Experimental results demonstrate that the proposed method can cull the hidden surfaces of the 3D scene correctly. The occlusion effect of the 3D scene can be well reproduced. The computational speed is better than that obtained using conventional methods but is still time-consuming.